Field notes contributed by Hank Zaletel, fall 1984 - Zaletel, Hanket al (1984)
Field notes were contributed by Hank Zaletel for fall 1984. 26 species in eight locations are listed within the report. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1984. Epson - sheet feed